Equipment inventories for owners and factory managers : standards, strategies and best practices - Keady, Robert (Wiley, 2013)
The National Institute of Science and Technology estimates that the loss of information between the construction of a building and the operation and maintenance of that building results in a 15.8 billion dollar loss annually. The loss is due to inconsistent standards for how to capture information about the facility and its equipment. Drawing upon his twenty plus years of experience in facility management and his intimate knowledge of CSI classification systems and standards, Robert Keady tackles this problem head-on. Using industry standards that are already in use in the AEC industry, Ke.